Distribution, habitat associations and conservation of the Eastern Cape rocky Sandelia bainsii (Perciform: Anabantidae) in the Great Fish River system - Sifundza, Delsy Sindy (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2020)
In South Africa, freshwater ecosystems are under pressure due to increasing anthropogenic factors degrading river systems. The Cape Fold, the lower Southern Temperate Highveld and the Amatolo "“ Winterberg Highlands freshwater ecoregions contain some of the heavily impacted river systems in the country. One such river system is the Great Fish River system, which has been affected by anthropogenic modification (hydrological modification, water pollution and invasion by non-native fish species). These modifications have raised conservation concerns on an imperilled anabantid fish, the Eastern Cape rocky Sandelia bainsii that is confined to the Kat and Koonap rivers, which are tributaries of the Great Fish River. Historically, the species was reportedly common and abundant, with a range spanning across seven river systems (Kowie, Great Fish, Keiskamma, Igoda, Gxulu, Buffalo and Nahoon rivers) in the Eastern Cape Province. However, surveys have indicated that the species has experienced decline in population size and distribution range, with localised extirpations being reported. This resulted in its listing on the IUCN Red List of threatened species as Endangered. The proposed shale gas exploration and potential infrastructure development in the Karoo basin, which encompasses the headwaters of the Kat River, represent a potential future threat to the remnant populations of this species. The aim of the present study was to review the past and present distribution range of S. bainsii, determine the habitat associations and assess the conservation of S. bainsii in the Great Fish River system. This information is essential for informing conservation and management decisions for this species in the Great Fish River system. This study undertook a comprehensive survey of the Kat and the Koonap rivers in 2017, and augmented this information with data from more recent surveys that were conducted from 2009 - 2014 to map the distributions freshwater fishes in the Great Fish River system. Data from these recent surveys (2009 "“ 2017) were compared with historical records (1961 "“ 2005) obtained from the South African Institute for Aquatic Biodiversity to evaluate changes in distribution patterns of S. bainsii. Historical records indicated that S. bainsii occurred at 11 localities in the Kat River and three localities in the Koonap River. Data from recent surveys indicated that the species has persisted at these historical localities, except one locality in the Koonap River where no individuals of S. bainsii were captured, despite the use of multiple sampling approaches and gears. Although the species still persists at two of the three historical localities in the Koonap River, the population sizes have considerably declined as the species was reportedly in high abundance at these localities in the 1980s. Factors threatening the continued existence of this species in the Koonap River likely include non-native species, extreme drought conditions and the associated excessive abstraction of water which has resulted in the drying of some of the refugia pools where the species was historically common and abundant. In contrast to the Koonap River, the 2017 survey indicated that in the Kat River, S. bainsii had a similar distribution range compared to historical records. The species occurred at 11 of the 41 localities that were sampled in the Kat River, and the sampled populations consisted of all size classes. Sandelia bainsii occurred with other native fish species in the system, including Labeo umbratus, Enteromius anoplus and Glossogobius callidus. A comparison of historical and recent data indicates that non-native fishes have likely not expanded their ranges in the Kat River. This is likely due to the presence of weirs and dams that have prevented upstream movement of non-native fish species L. aeneus, C. gariepinus and T. sparrmanii which are now abundant in the lower Kat and mainstem Great Fish River. Surveys from the present study indicated that although S. bainsii still persists within the Kat River, there are a number of factors that pose a considerable threat to the continued existence of this species in the Great Fish River system. Chapter 3 evaluated the habitat associations of S. bainsii based on 10 physical and chemical variables and distribution data collected from 30 localities in the Upper Kat River and seven of its tributaries. A non-metric multidimensional scaling model was used to assess the distribution patterns of S. bainsii in relation to environmental variables. Furthermore, a negative binomial generalised linear model (GLM) was used to assess the relationship between the abundance of S. bainsii and environmental variables. Results from the present study indicated that S. bainsii was a habitat generalist as the distribution of this species showed no specific association with any of the habitat variables that were considered in this study. The species occurred in a wide range of habitats, including rocky sections in the upper Kat River and its tributaries as well as the mainstem sections. The GLM however indicated that the abundance of S. bainsii was negatively associated with increasing conductivity. In addition, the Kat River contains multiple weirs of variable sizes. Future studies should therefore evaluate the effects of these weirs on population fragmentation, gene flow and long-term evolutionary potential of S. bainsii through the application of techniques such as mitochondrial DNA and microsatellites.
Keywords: Anabantidae -- South Africa -- Great Fish River; Perciformes -- South Africa -- Great Fish River; Labyrinth fishes -- South Africa -- Great Fish River; Fishes -- Effect of human beings on -- South Africa -- Great Fish River; Fish populations -- South Africa -- Great Fish River; Fish declines -- South Africa -- Great Fish River; Fish populations -- Monitoring -- South Africa -- Great Fish River; Anabantidae -- Evolution -- South Africa -- Great Fish River; Gene flow; Mitochondrial DNA; Microsatellites (Genetics); Eastern Cape rocky Sandelia bainsii; Freshwater ecology -- South Africa -- Great Fish River